Early weight-bearing after anterior cruciate ligament reconstruction with hamstring grafts induce femoral bone tunnel enlargement: a prospective clinical and radiographic study - Tajima, Takuya (BMC Musculoskelet Disord, 2019)
BACKGROUND: Bone tunnel enlargement following primary anterior cruciate ligament (ACL) reconstruction with soft tissue graft might be a severe disadvantage for revision surgery. The postoperative rehabilitation protocol including the non-weight-bearing periods were different depending on the surgeon or institute. To determine the relationship between femoral bone tunnel enlargement and the postoperative non-weight-bearing period after double-bundle ACL reconstruction with hamstring grafts. METHODS: Forty-two patients who underwent primary double-bundle ACL reconstruction with hamstring grafts were divided into two postoperative non-weight-bearing protocol groups: 1-week non-weight-bearing postoperatively (group A, n = 19); and 2-week non-weight-bearing (group B, n = 18). Five cases were excluded due to additional knee injury, pregnancy, and lost to follow-up. Bone tunnel enlargement was evaluated by computed digital radiographs (anteroposterior (A-P) and lateral views) taken on the first postoperative day and at 12 months. Each tunnel diameter was shown as a percentage to the maximum joint width of the proximal tibia in the A-P view, or a percentage of the maximum diameter of the patella in the lateral view. To determine the incidence of tunnel enlargement, percentage diameter changes of more than 10% were defined as an enlarged tunnel. The magnitude of tunnel enlargement and the standard clinical evaluation were also evaluated. RESULTS: There were no significant differences between groups in the incidences of anteromedial and posterolateral bone tunnel enlargement, both in the A-P and lateral views (2 × 2 Chi-squared test). The magnitude of femoral posterolateral bone tunnel enlargement was significantly greater in group A in the A-P view (p = 0.01) and lateral view (p = 0.03) (Mann Whitney U-test). Twelve months after surgery, the Lysholm score and Tegner activity level scale were not significantly different between the groups. CONCLUSIONS: This prospective, clinical and radiographical study showed that early weight-bearing protocol after double-bundle ACL reconstruction with hamstring grafts might have the potential risk of significant postoperative femoral bone tunnel enlargement of the posterolateral bundle. There was no significant difference in clinical outcomes by postoperative non-weight-bearing period. To reduce and prevent the femoral bone tunnel enlargement, the comprehensive management could be considered and required to establish the suitable early stage rehabilitation protocol after surgery. TRIAL REGISTRATION: Trial registration number; UMIN000036212. Scientific title: Prospective comparisons of femoral tunnel enlargement with two different postoperative non weight bearing periods after double-bundle anterior cruciate ligament reconstruction with hamstring grafts. Registered date: 15 Mar 2019 (retrospectively registered).